The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/5262896
|View full text |Cite
|
Sign up to set email alerts
|

Different Brain Activation after Acupuncture at Combined Acupoints and Single Acupoint in Hypertension Patients: An Rs-fMRI Study Based on ReHo Analysis

Abstract: Background Acupuncture is proved to be effective on hypertension by numerous studies and resting-state functional magnetic resonance imaging (Rs-fMRI) is a widely used technique to study its mechanism. Along with lower blood pressure, patients with hypertension receiving acupuncture also presented improvement in function of cognition, emotion, language, sematic sensation, and so on. This study was a primary study to explore the acting path of acupuncture at combined acupoints in stimulated brain areas related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Wang et al reported that the combination of multiple acupoints resulted in improved the score of the Pittsburgh sleep quality index and Athens Insomnia Scale via regulation of the activity of the brain area related to sleep experience [ 39 ]. The RCT which enrolled 30 patients with hypertension showed that the combined acupuncture points LR3 and KI3 can activate a wider area of the brain than a single point acupuncture based on the resting-state functional magnetic resonance imaging scan [ 41 ]. Gao et al demonstrated that stimulating acupoint combination in slow transit constipation mice showed higher defecation grain number and intestinal propulsion rate compared with a single acupoint [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that the combination of multiple acupoints resulted in improved the score of the Pittsburgh sleep quality index and Athens Insomnia Scale via regulation of the activity of the brain area related to sleep experience [ 39 ]. The RCT which enrolled 30 patients with hypertension showed that the combined acupuncture points LR3 and KI3 can activate a wider area of the brain than a single point acupuncture based on the resting-state functional magnetic resonance imaging scan [ 41 ]. Gao et al demonstrated that stimulating acupoint combination in slow transit constipation mice showed higher defecation grain number and intestinal propulsion rate compared with a single acupoint [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as reported by Zhang et al, the acupoint combination of LR3 and KI3 could generate greater synergistic effects in patients with hypertension than that of a single acupoint (LR3 or KI3). The results of resting-state fMRI revealed that acupuncture from LR3 and KI3 could activate broader brain areas in comparison to the single LR3 or KI3 [44]. In view of the two advantages of acupoint combination, it is important to ascertain the acupoint combination instead of the single acupoint.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed previous acupuncture treatment for sciatica in MEDLINE (PubMed) since 1970 and selected acupoints that were effective for treatment (Liu & Chen, 2017). We chose to use a combined acupoint treatment strategy, considering that treatment using acupoint combinations may achieve a synergistic effect in the brain (Zhang et al, 2019(Zhang et al, , 2016 (Qin, Liu, Liu, Wu, Zhai, & Liu, 2015).…”
Section: Methodsmentioning
confidence: 99%